Biochemical changes in cotton plants by Arbuscular Mycorrhizal colonization - Damodaran, P. N; Udaiyan, K.; Jee, H. J. (Research in Biotechnology, 2010)
Biochemical changes in ten cultivars of cotton (Gossypium hirsutum L. Merr. ) in relation with arbuscular mycorrhizal (AM) colonization was studied.Ã‚Â Proteins, sugars, amino acids and phenols in both leaves and roots were quantified and compared with the mycorrhization levels of the cultivars. Cultivars showed varying levels of mycorrization which correlated with the biochemical levels of the plants. It is concluded that cultivars which are more mycorrhizal do show increased levels of phenols and proteins which in turn help them to resist pathogenesis.